Ethical environments in university and plagiarism evidence from Indonesia - SeTin SeTin; Santy Setiawan; Debbianita Debbianita (International Journal of Evaluation and Research in Education (IJERE), 2022)
Accountant educators are among those who are blamed for scandals in practice because the journey of ethical learning is believed to begin in the college. Therefore, this study investigated the perceptions of accountant educators about the ethical environment in colleges and plagiarism behavior. More specifically, this study compared the perceptions of accountant educators in: i) State and private universities; ii) A-accredited universities and B-accredited universities, and examined the relationship between ethical environment and plagiarism. Comparative analysis (t test and one-way ANOVA) and regression analysis methods are used for data analysis. Based on the responses of 147 accountant educators, it was found that accountant educators who work at state universities and at A-accredited universities perceive an ethical environment significantly stronger than accountant educators who work at private universities and at B-accredited universities. Average of the respondents perceived plagiarism behavior as unethical. There were differences in the perception of the ethical environment in terms of gender and academic position, and there were significant differences in plagiarism behavior in terms of type and institutional accreditation, working period, and academic position. The findings also showed that the perception of the ethical environment has a negative effect on plagiarism behavior.